Magic misfits : the second story - Harris, Neil Patrick, 1973-; Azam, Alec (Harris, Neil Patrick, 1973- Magic Misfits, 2018)
Leila and the other Magic Misfits have the opportunity to perform with a famous stage psychic known as Madame Esmeralda, who may hold secrets to Leila's past.